Method for manufacturing a catalyst layer for a fuel cell and method for manufacturing a fuel cell
By using inclinedly arranged fibrous conductive members and catalyst particles in the fuel cell catalytic layer, the problem of conductive nanopillars embedded in the electrolyte membrane under the action of external forces is solved, low contact resistance and high gas diffusion, and the output performance of the fuel cell is improved.
Patent Information
- Application Number
- JP2023091126
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-12-28
- Filing Date
- 2023-06-01
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2038-12-26
AI Technical Summary
Under the action of external forces, the catalytic layer of the existing fuel cell can easily cause the end of the conductive nanopillars to be embedded in the electrolyte membrane or gas diffusion layer, resulting in an increase in gas diffusion and contact resistance, affecting battery performance.
A catalytic layer composed of fibrous conductive members and catalyst particles is arranged inclined relative to the surface of the catalytic layer, with an average length direction pointing in a specific direction, and its inclination angle and linearity are controlled to ensure uniform thickness and good contact.
The contact resistance between the catalytic layer and the gas diffusion layer is improved, the gas diffusion is enhanced, and the output performance of the fuel cell is improved.
Smart Images

Figure 0007627856000002 
Figure 0007627856000003 
Figure 0007627856000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a catalyst layer for a fuel cell and a fuel cell. [Background technology]
[0002] A fuel cell includes a membrane electrode assembly having an electrolyte membrane and a pair of electrodes sandwiching the electrolyte membrane. Each of the pair of electrodes includes, in order from the electrolyte membrane side, a catalyst layer and a gas diffusion layer.
[0003] Patent Document 1 proposes using a catalyst layer containing conductive nanocolumns (hereinafter simply referred to as columns) oriented in a direction approximately perpendicular to the surface direction of an electrolyte membrane (catalyst layer) and a catalyst supported on the columns, and interposing an embedding prevention layer between the catalyst layer and the electrolyte membrane.
[0004] The catalyst layer is formed by forming pillars oriented in a direction substantially perpendicular to the surface of a substrate by chemical vapor deposition, and then transferring the pillars on the substrate to an electrolyte membrane. The embedding prevention layer is provided to prevent a decrease in the catalyst utilization rate due to embedding of the ends of the pillars in the electrolyte membrane during the transfer.
[0005] Patent Document 2, like Patent Document 1, uses conductive nanocolumns and a catalyst supported on the columns, and proposes that the columns be oriented at an inclination of 60° or less with respect to the surface direction of the electrolyte membrane, and that one end of the columns be embedded in the electrolyte membrane.
[0006] Patent Document 3 discloses a catalyst layer containing long carbon fibers and a catalyst. It proposes stacking the long carbon fibers lying down on the electrolyte membrane in one direction, arranging the catalyst layer so that the length direction of the long carbon fibers is perpendicular to the gas flow direction, and changing the height at which the long carbon fibers are stacked with respect to the gas flow direction. This generates gas turbulence, improving the gas diffusion of the catalyst layer. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2013 / 065396 [Patent Document 2] JP 2007-257886 A [Patent Document 3] Japanese Patent Application Publication No. 3-145062 Summary of the Invention
[0008] The pillars in Patent Document 1 are oriented in a direction substantially perpendicular to the surface direction of the catalyst layer (electrolyte membrane), and both ends of the pillars are in contact with the electrolyte membrane and the gas diffusion layer, respectively. On the other hand, an external force may be applied in the thickness direction of the membrane electrode assembly during the manufacture of a membrane electrode assembly, a single cell, or a stack (cell stack) of a plurality of single cells. When the above-mentioned external force is applied, stress is concentrated at both ends of the pillars, which may cause problems such as bending the pillars or their ends piercing the electrolyte membrane or the gas diffusion layer. When the above-mentioned problems occur, the gaps (gas paths) formed in the catalyst layer become uneven, and the gas diffusion property decreases in a part of the catalyst layer.
[0009] The pillars in Patent Document 2 are oriented obliquely with respect to the surface direction of the electrolyte membrane, and one end of the pillar on the electrolyte membrane side is embedded in the electrolyte membrane. As described above, when an external force is applied to the pillars in the thickness direction, the stress applied to the pillars is directly applied to the electrolyte membrane, which leads to damage to the electrolyte membrane. Furthermore, as described above, when an external force is applied to the pillars in the thickness direction, the pillars are oriented obliquely, so that stress is concentrated on the side of the pillars, which causes the pillars to bend. When such bending occurs, the distance between adjacent pillars is reduced, which causes deviation of the gas path and leads to a decrease in gas diffusibility.
[0010] In Patent Document 3, the height at which the long carbon fibers are stacked (the thickness of the catalyst layer) is changed, which reduces the contact area between the gas diffusion layer and the catalyst layer, and this may increase the contact resistance. On the other hand, if the height at which the long carbon fibers are stacked is made uniform, the contact resistance between the catalyst layer and the gas diffusion layer is reduced, but the gas diffusibility in the thickness direction of the catalyst layer is reduced.
[0011] Furthermore, when the catalyst layer described in Patent Document 2 in which the long carbon fibers lying down on the electrolyte membrane are aligned in one direction is used and gas is caused to flow along the length of the long carbon fibers, the gas diffusibility in the surface direction of the catalyst layer is improved but the gas diffusibility in the thickness direction of the catalyst layer is low.
[0012] One aspect of the present disclosure relates to a catalyst layer for a fuel cell having a uniform thickness, the catalyst layer including a fibrous conductive member and a catalyst particle, the fibrous conductive member being inclined with respect to a surface direction of the catalyst layer, and the length direction of the fibrous conductive member being oriented, on average, in a first direction.
[0013] Another aspect of the present disclosure relates to a fuel cell including a membrane electrode assembly, and a first separator and a second separator sandwiching the membrane electrode assembly. The membrane electrode assembly includes an electrolyte membrane, and a first electrode and a second electrode sandwiching the electrolyte membrane. The first electrode includes, in order from the electrolyte membrane side, a first catalyst layer and a first gas diffusion layer. The first catalyst layer is the above-mentioned catalyst layer.
[0014] According to the present disclosure, it is possible to provide a catalyst layer that has low contact resistance with a gas diffusion layer and excellent gas diffusivity, and also to provide a fuel cell with excellent output characteristics. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is an explanatory diagram for explaining how to determine a first reference line (first direction) using a main surface of a catalyst layer. [Diagram 2] 4 is an explanatory diagram for explaining a method for calculating the linearity Lp and the inclination angle θc of a fibrous conductive member using a cross section of a catalyst layer. FIG. [Diagram 3]FIG. 4 is an explanatory diagram illustrating an example of a catalyst ink application process. [Figure 4] 1 is a cross-sectional view showing a schematic structure of a single cell of a fuel cell according to an embodiment of the present disclosure. [Diagram 5] 1 is a diagram showing a schematic view of the inside of a catalyst layer according to an embodiment of the present disclosure as viewed from its surface direction (direction perpendicular to a first direction). [Figure 6] FIG. 6 is a diagram showing a schematic view of the inside of the catalyst layer shown in FIG. 5 as viewed from the gas diffusion layer side. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] [Catalyst layer for fuel cells] A catalyst layer for a fuel cell according to an embodiment of the present disclosure has a uniform thickness and includes a fibrous conductive member and catalyst particles. The fibrous conductive member is inclined with respect to the surface direction of the catalyst layer (electrolyte membrane), and the length direction of the fibrous conductive member is oriented, on average, in a first direction.
[0017] The term "the length direction of the fibrous conductive members is oriented in the first direction on the average" means that, when the catalyst layer is viewed from a direction perpendicular to the surface direction of the catalyst layer, the angle θ between the first reference line extending in the first direction and the length direction of the fibrous conductive members is 0.05 mm. d1 This means that the average angle is 30° or less.
[0018] The first reference line (first direction) is obtained as follows, using Fig. 1. Fig. 1 is an explanatory diagram explaining how to obtain the first reference line (first direction) using the main surface of the catalyst layer 120 (see Fig. 2). Fig. 1 shows only a part of the fibrous conductive members 121 in the region R1 of the first main surface 120X on the gas diffusion layer side.
[0019] First, the gas diffusion layer is removed from the membrane electrode assembly 100 (see FIG. 4) to expose the first main surface 120X on the gas diffusion layer side of the catalyst layer 120. The first main surface 120X is photographed using a scanning electron microscope (SEM).
[0020] Using the obtained SEM image, an area R1 (50 μm × 50 μm) is arbitrarily determined as an area facing the gas flow path on first main surface 120X of catalyst layer 120, where, for example, 20 or more fibrous conductive members 121 can be confirmed. Ten identifiable fibrous conductive members 121 are arbitrarily selected from area R1. A tangent line L1 is drawn at midpoint C1 of the observable length of the ten fibrous conductive members 121.
[0021] In the above, three regions R1 are determined so as not to overlap each other, and ten tangent lines L1 are obtained for each region in the same manner. The directions of the obtained 30 tangent lines L1 are averaged, the average direction is set as the first direction, and the straight line extending in the average direction (first direction) is set as the first reference line BL1.
[0022] When the gas flow path has a plurality of straight portions because the gas flow path has a serpentine shape, for example, the three regions R1 may be determined within a range facing one straight portion on the first main surface 120X of the catalyst layer 120.
[0023] The angle θ between a first reference line extending in a first direction and the length direction of the fibrous conductive member when the catalyst layer is viewed from a direction perpendicular to the surface direction of the catalyst layer. d1 is calculated as follows:
[0024] For each of the 30 tangent lines L1 obtained above, the angle (0° to 90°) between the first reference line BL1 obtained above and the tangent line L1 is calculated. The average of the calculated angles is called the angle θ d1 The obtained angle θ d1 When the angle is 30° or less, it is assumed that the length direction of the fibrous conductive members is oriented, on average, in the first direction.
[0025] The term "the fibrous conductive member is inclined with respect to the surface direction of the catalyst layer" means that the fibrous conductive member is present in the catalyst layer at an incline with respect to the surface direction of the catalyst layer while maintaining its linearity. Note that the linearity of the fibrous conductive member is maintained means that the fibrous conductive member is not significantly bent, and the linearity L calculated by the method described below is pFrom the viewpoint of further improving gas diffusion, the linearity L p (Average value) is preferably 0.7 or more.
[0026] Since the length direction of the fibrous conductive members is oriented in the first direction on average, the gas diffusion in the surface direction of the catalyst layer is improved. Furthermore, since the fibrous conductive members are inclined with respect to the surface direction of the catalyst layer, good gas diffusion is also obtained in the direction perpendicular to the surface direction of the catalyst layer (thickness direction). In the above catalyst layer, voids (gas paths) can be sufficiently formed within the catalyst layer, and gas can be effectively diffused throughout the entire catalyst layer.
[0027] Since the fibrous conductive member is inclined with respect to the surface direction of the catalyst layer, bending of the fibrous conductive member and piercing of the electrolyte membrane, etc. due to the application of an external force in the thickness direction of the membrane electrode assembly (catalyst layer) are suppressed. This suppresses a decrease in gas diffusibility in a part of the catalyst layer caused by bending of the fibrous conductive member and piercing of the electrolyte membrane, etc. As a result, the output characteristics of the fuel cell are improved. Furthermore, the possibility that the conductivity of the fibrous conductive member will be affected by bending of the fibrous conductive member and piercing of the electrolyte membrane, etc. is eliminated. Even without providing an embedding prevention layer, embedding of the ends of the fibrous conductive member into the electrolyte membrane when the catalyst layer is transferred to the electrolyte membrane is suppressed.
[0028] The catalyst layer is a layer of uniform thickness formed, for example, using a catalyst ink described later. Thus, a sufficient contact area between the gas diffusion layer and the catalyst layer is ensured, and an increase in resistance due to a small contact area is suppressed. The catalyst layer having a uniform thickness means that the difference (absolute value) between 10 measured values obtained when determining the thickness T (see FIG. 2) of the catalyst layer described later and their average value is 25% or less of the average value. In this case, it is sufficient that the difference between the average value and 6 or more of the 10 measured values is 25% or less.
[0029] Length of fibrous conductive material L f and the thickness T of the catalyst layer are expressed by the following formula: L fIt is preferable that L / T≦3 is satisfied. In this case, a catalyst layer is easily formed in which the fibrous conductive members are inclined with respect to the surface direction of the catalyst layer and the length direction of the fibrous conductive members is oriented in the first direction on average. In this case, the fibrous conductive members can be easily inclined with respect to the surface direction of the catalyst layer while maintaining their linearity, so that the gas diffusion layer in the thickness direction of the catalyst layer is further improved. From the viewpoint of further improving the gas diffusion property of the catalyst layer, L f It is more preferable that / T is 0.25 or more and 2.0 or less.
[0030] Length of fibrous conductive material L f is the average fiber length, which is determined by randomly selecting 10 fibrous conductive members from the catalyst layer and averaging the fiber lengths of these fibrous conductive members. Note that the fiber length of the fibrous conductive member refers to the length of a straight line connecting one end of the fibrous conductive member to the other end of the fibrous conductive member.
[0031] Length of fibrous conductive material L f is preferably 0.2 μm or more and 20 μm or less, more preferably 0.5 μm or more and 10 μm or less. In this case, even in a thin catalyst layer (for example, thickness T is 10 μm or less), the fibrous conductive member can be easily inclined with respect to the surface direction of the catalyst layer. In addition, by using a short fibrous conductive member within the above range, both ends of the fibrous conductive member are prevented from contacting the electrolyte membrane and the gas diffusion layer, respectively, in the catalyst layer. This further prevents the ends of the fibrous conductive member from being embedded in the electrolyte membrane when the catalyst layer is transferred to the electrolyte membrane, and further prevents the fibrous conductive member from piercing the electrolyte membrane, etc., when an external force is applied in the thickness direction of the membrane electrode assembly.
[0032] The thickness T of the catalyst layer is an average thickness, and is obtained by averaging the distances when a straight line is drawn along the thickness direction of the catalyst layer from one main surface to the other main surface for any ten points on the cross section of the catalyst layer.
[0033] The thickness T of the catalyst layer is preferably thin in consideration of the miniaturization of the fuel cell, but is preferably not excessively thin in terms of strength. The thickness T of the catalyst layer is, for example, 1 μm or more and 50 μm or less, and preferably 2 μm or more and 20 μm or less.
[0034] The inclination angle θ of the fibrous conductive member with respect to the surface direction of the catalyst layer c (see FIG. 2) is preferably 80° or less, and more preferably 70° or less. c When the inclination angle θ is 80° or less, the gas diffusibility in the surface direction of the catalyst layer is further improved in addition to the thickness direction of the catalyst layer. c When the angle is 70° or less, bending of the fibrous conductive members and piercing of the electrolyte membrane or the like due to application of an external force in the thickness direction of the membrane electrode assembly are further suppressed.
[0035] Linearity L of fibrous conductive material p and the inclination angle θ c The linearity L of the fibrous conductive member can be calculated as follows, using FIG. p Calculation method and inclination angle θ c 2 is an explanatory diagram for explaining a method for calculating the fibrous conductive member 121 using a cross section of a catalyst layer 120. In FIG. 2, only a part of the fibrous conductive members 121 is shown.
[0036] First, a cross section of the catalyst layer 120 having a first main surface 120X on the gas diffusion layer side and a second main surface 120Y on the electrolyte membrane side, taken in the thickness direction and along the first direction, is photographed with a scanning electron microscope (SEM).
[0037] From the obtained SEM image, a square region R2 is determined in which, for example, 20 or more fibrous conductive members 121 can be confirmed, and one side of the region R2 is the thickness T of the catalyst layer 120. Region R2 can be determined as follows. First, a straight line is drawn along the thickness direction of the catalyst layer 120. The intersection of this line and the second main surface 120Y is set as one of the vertices of the square representing region R2. Next, two sides of length T that intersect perpendicularly with each other are drawn from this vertex, and the remaining two sides are further drawn so that a square including these two sides is formed.
[0038] Next, ten identifiable fibrous conductive members 121 are arbitrarily selected from within region R2. For each of the ten fibrous conductive members 121, one end of the observable length portion is connected to the other end with a straight line, and the length L of the line is s Also, find the actual length L of the observable part. r L r L for s Ratio of: L s / L r The linearity ratio L p Let us assume that.
[0039] In the above, the three regions R2 are determined so as not to overlap each other, and the linearity L of the ten fibrous conductive members 121 is set to each of the three regions R2. p The linearity L of the 30 fibrous conductive members 121 is calculated. p Calculate the average value of the linearity L p When the average value is 0.6 or more, it is determined that the linearity of the fibrous conductive member 121 is ensured. p If the average value is less than 0.6, it is determined that the fibrous conductive member 121 is bent, and the inclination angle θ described below cannot be obtained.
[0040] After confirming that the linearity of the fibrous conductive member is ensured by the linearity ratio described above, the inclination angle θ of the fibrous conductive member is c can be calculated as follows using FIG. 2.
[0041] For each of the ten fibrous conductive members 121 selected from each of the three regions R2, a tangent line L2 is drawn at the midpoint C2 of the observable length. The angle (0° or more and 90° or less) between this tangent line L2 and the first main surface 120X is defined as the inclination angle θ of the fibrous conductive member 121. c The inclination angle θ of a total of 30 fibrous conductive members 121 is c In addition, when the first main surface 120X has projections and recesses, the surface perpendicular to the thickness direction of the catalyst layer 120 or the smooth second main surface 120Y is inclined at an inclination angle θ c This may be used as a criterion for determining
[0042] The inclination direction of the fibrous conductive members does not have to be uniform in a cross section along the thickness direction and the first direction of the catalyst layer, but from the viewpoint of improving the gas diffusion property of the catalyst layer, it is preferable that the inclination direction of the fibrous conductive members is uniform in a cross section along the thickness direction and the first direction of the catalyst layer.
[0043] In addition, in a cross section along the thickness direction of the catalyst layer and the first direction, the inclination direction of the fibrous conductive members is uniform means that, in a cross section along the thickness direction of the catalyst layer and the first direction, the length directions of the fibrous conductive members are oriented on average in the second direction. In a cross section along the thickness direction of the catalyst layer and the first direction, the length directions of the fibrous conductive members are oriented on average in the second direction means that, when the catalyst layer is viewed from a direction perpendicular to the cross-sectional direction, the angle θ between a second reference line extending in the second direction and the length directions of the fibrous conductive members is oriented on average in the second direction. d2 This means that the angle is 30° or less.
[0044] The second reference line (second direction) is the linearity L of the fibrous conductive member. p and the inclination angle θ c The second reference line BL2 is determined by using a total of 30 tangent lines L2 obtained when determining the second reference line BL2. Specifically, the directions of the obtained 30 tangent lines L2 are averaged, the averaged direction is set as the second direction, and a straight line extending in the averaged direction (second direction) is set as the second reference line BL2.
[0045] When the catalyst layer is viewed in a direction perpendicular to the cross-sectional direction, an angle θ is formed between a second reference line BL2 extending in the second direction and the length direction of the fibrous conductive member. d2 is calculated as follows:
[0046] For each of the 30 tangent lines L2 obtained above, the angle (0° to 90°) between the reference line BL2 obtained above and the tangent line L2 is calculated. The average of the calculated angles is called the angle θ d2 The obtained angle θ d2 When the angle is 30° or less, it is assumed that the length direction of the fibrous conductive members is oriented in the second direction on average.
[0047] Diameter D of the fibrous conductive material fis preferably 200 nm or less, more preferably 5 nm or more and 200 nm or less, and further preferably 8 nm or more and 100 nm or less. In this case, the volume ratio of the fibrous conductive members in the catalyst layer can be reduced, and a sufficient gas path can be secured, thereby further improving gas diffusibility.
[0048] Diameter D of the fibrous conductive material f is determined by randomly taking 10 fibrous conductive members from the catalyst layer and averaging their diameters. The diameter is the length in the direction perpendicular to the longitudinal direction of the fibrous conductive members.
[0049] Length of fibrous conductive material L f and the diameter D of the fibrous conductive member f And the relation:D f / L f It is preferable that the above condition is satisfied. In this case, a satisfactory gas diffusibility can be obtained throughout the entire catalyst layer.
[0050] From the viewpoint of improving electrical conductivity, D f / L f is more preferably 0.002 or more and less than 1.
[0051] Examples of the fibrous conductive member include carbon fibers such as vapor grown carbon fiber (VGCF), carbon nanotubes (CNT), and carbon nanofibers.
[0052] At least a portion of the catalyst particles is supported on the fibrous conductive member. The catalyst particles are preferably supported on a particulate conductive member (described later) in addition to the fibrous conductive member. This is because the catalyst particles are more likely to come into contact with the gas, thereby increasing the efficiency of the oxidation or reduction reaction of the gas.
[0053] The catalyst particles are not particularly limited, and examples thereof include catalyst metals such as alloys or simple substances selected from Sc, Y, Ti, Zr, V, Nb, Fe, Co, Ni, Ru, Rh, Pd, Pt, Os, Ir, lanthanide series elements, and actinide series elements. For example, catalyst particles used in the anode include Pt-Ru alloys, etc.; catalyst metals used in the cathode include Pt and Pt-Co alloys, etc.
[0054] From the viewpoint of shortening the conductive path and further increasing the conductivity, it is preferable that the catalyst layer further contains a particulate conductive member. The particulate conductive member is not particularly limited, but carbon black is preferable because of its excellent conductivity. Examples of carbon black include acetylene black, ketjen black, thermal black, furnace black, channel black, etc. The particle size (or the length of the structure composed of a plurality of connected primary particles) is not particularly limited, and those conventionally used in the catalyst layer of a fuel cell can be used.
[0055] The content of the particulate conductive member in the catalyst layer is preferably 40 parts by mass or less, more preferably 5 parts by mass or more and 35 parts by mass or less, and even more preferably 10 parts by mass or more and 30 parts by mass or less, per 100 parts by mass of the total of the fibrous conductive member and the particulate conductive member. In this case, the conductivity can be increased while ensuring good gas diffusibility of the entire catalyst layer.
[0056] From the viewpoint of improving the reactivity of the catalyst layer, it is preferable that the catalyst layer further contains a proton conductive resin. In this case, the proton conductive resin covers at least a part of the fibrous conductive member and the catalyst particles. Since the fibrous conductive member is inclined with respect to the surface direction of the catalyst layer, the influence on the reactivity (proton conductivity) of the catalyst layer caused by bending of the fibrous conductive member or piercing into the electrolyte membrane or the like due to the application of an external force in the thickness direction of the membrane electrode assembly is suppressed.
[0057] The proton conductive resin is not particularly limited, but examples thereof include perfluorocarbon sulfonic acid polymers and hydrocarbon polymers. Among them, perfluorocarbon sulfonic acid polymers and the like are preferred because of their excellent heat resistance and chemical stability. An example of a perfluorocarbon sulfonic acid polymer is Nafion (registered trademark). The proton conductive resin may further coat at least a portion of the particulate conductive member.
[0058] The content of the fibrous conductive member in the catalyst layer is preferably 15 to 65 parts by mass, more preferably 20 to 55 parts by mass, relative to 100 parts by mass of the total of the catalyst particles, the particulate carbon material, and the proton conductive resin, because the fibrous conductive member is more likely to be arranged in a desired state, and gas diffusion and electrochemical reaction efficiency are more likely to be improved.
[0059] The catalyst layer can be formed, for example, by applying a catalyst ink containing fibrous conductive members and catalyst particles to the surface of the electrolyte membrane and drying it. Alternatively, the catalyst ink may be applied to a transfer substrate sheet, dried to form a catalyst layer, and the catalyst layer formed on the substrate sheet may be transferred to the electrolyte membrane. Since the fibrous conductive members are inclined with respect to the surface direction of the catalyst layer, embedding of the fibrous conductive members in the electrolyte membrane during transfer of the catalyst layer is suppressed even without disposing an embedding prevention layer on the surface of the electrolyte membrane. As the substrate sheet, for example, a sheet having a smooth surface such as polyethylene terephthalate (PET) or polypropylene is preferably used.
[0060] The catalyst ink contains a dispersion medium other than the fibrous conductive members and catalyst particles. The dispersion medium may be, for example, water, ethanol, propanol, etc. The catalyst ink may further contain particulate conductive members, a proton conductive resin, etc.
[0061] The coating method is preferably a screen printing method or a coating method using various coaters such as a blade coater, a knife coater, or a gravure coater.
[0062] The above coating method makes it easy to tilt the fibrous conductive members and to control the tilt direction of the fibrous conductive members. Coating in one direction makes it easy to form a catalyst layer in which the fibrous conductive members are tilted with respect to the surface direction of the catalyst layer and the length direction of the fibrous conductive members is oriented in the first direction on average. Coating in one direction also makes it easy to align the tilt direction of the fibrous conductive members in a cross section along the thickness direction of the catalyst layer.
[0063] By keeping the coating amount and coating speed constant, a catalyst layer with a uniform thickness can be easily formed.
[0064] In forming a catalyst layer by applying catalyst ink, L f It is preferable to adjust the length of the fibrous conductive member and the thickness of the catalyst layer so that / T is 3 or less. In this case, it is easy to form the catalyst layer. In particular, it is easy to incline the fibrous conductive member with respect to the surface direction of the catalyst layer. The thickness of the catalyst layer can be adjusted by changing the amount of catalyst ink applied, etc.
[0065] Inclination angle θ of fibrous conductive member c can be adjusted by changing, for example, the length of the fibrous conductive member, the amount of catalyst ink applied, the application speed, the viscosity, etc.
[0066] [Fuel cell] A fuel cell according to an embodiment of the present disclosure includes a membrane electrode assembly, and a first separator and a second separator sandwiching the membrane electrode assembly, and the membrane electrode assembly includes an electrolyte membrane, and a first electrode and a second electrode sandwiching the electrolyte membrane. The first electrode includes, in order from the electrolyte membrane side, a first catalyst layer and a first gas diffusion layer. The first catalyst layer is the above-mentioned catalyst layer. By including the above-mentioned catalyst layer, a fuel cell with excellent output characteristics can be obtained. One of the first electrode and the second electrode is an anode, and the other is a cathode.
[0067] The first separator has a first gas flow channel, and the first direction is preferably oriented along an average flow channel direction of the first gas flow channels when viewed from the stacking direction of the membrane electrode assembly. The first gas flow channel may be composed of one flow channel or may be composed of multiple flow channels arranged in parallel.
[0068] The above-mentioned first direction being oriented in the average flow path direction of the first gas flow path means that, when viewed from the stacking direction of the membrane electrode assembly, the angle θ between the first direction and the average flow path direction of the first gas flow path is smaller than the angle θ g The angle θ is 45° or less. g is preferably 30° or less, and more preferably 10° or less. The average flow path direction of the first gas flow path refers to the direction from one end (gas inlet) to the other end (gas outlet) of the first gas flow path.
[0069] In the above catalyst layer, the length direction of the fibrous conductive members is oriented in the first direction on average, so that many voids are formed in the catalyst layer along the first direction. In addition, the first direction is oriented in the average flow path direction of the first gas flow path. Therefore, gas is smoothly supplied from the first gas flow path into the catalyst layer, and excess gas is smoothly discharged from the catalyst layer to the first gas flow path. This further improves the gas diffusibility in the surface direction of the catalyst layer.
[0070] From the viewpoint of improving gas diffusion in the planar direction of the catalyst layer, it is preferable that the first gas flow path has a plurality of first straight portions facing in a first direction, and that the ratio of the total length of the plurality of first straight portions to the total length of the first gas flow path is 80% or more and 100% or less.
[0071] When the first gas flow path has a serpentine shape, the first gas flow path has a plurality of first straight portions facing a first direction and a plurality of first turn portions connecting ends of adjacent first straight portions. Gas flows in a meandering manner through the first turn portions of the first straight portions. The first straight portion may be composed of one flow path, or may be composed of a plurality of flow paths arranged in parallel.
[0072] In the first catalyst layer, the fibrous conductive members are preferably inclined in the same direction so that the end of the fibrous conductive member on the first gas diffusion layer side is located downstream of the end of the fibrous conductive member on the electrolyte membrane side in the average flow path direction of the first gas flow path. In this case, the gas diffusibility in the surface direction of the catalyst layer is further improved. In addition, when the first catalyst layer is a cathode catalyst layer, water generated in the catalyst layer is easily discharged to the outside through the gas diffusion layer along the gas flow, and good gas diffusibility is maintained throughout the catalyst layer.
[0073] In the first catalyst layer, it is more preferable that the inclination direction of the fibrous conductive members is aligned so that the end of the fibrous conductive member facing the first gas diffusion layer is located downstream of the first straight portion of the first gas flow path relative to the end of the fibrous conductive member facing the electrolyte membrane.
[0074] Here, an example of a process of applying a catalyst ink containing a fibrous conductive member to the surface of an electrolyte membrane when a first separator having a serpentine-type first gas flow path is used will be described with reference to FIG. 3. The dashed line in FIG. 3 indicates a first gas flow path 360 when viewed from the stacking direction when a first catalyst layer, a first gas diffusion layer, and a first separator are sequentially arranged on one surface of the electrolyte membrane 110, and the first gas flow path 360 has a first straight portion 361 and a first turn portion 362. The arrows in the dashed line indicate the direction of gas flow. The electrolyte membrane 110 has a plurality of regions separated by dashed lines, and each of the plurality of regions includes one first straight portion 361. When applying a catalyst ink containing a fibrous conductive member to the surface of the electrolyte membrane 110 using various coaters or the like, the direction in which the catalyst ink is applied to the electrolyte membrane 110 may be changed for each region in accordance with the direction of gas flow in the first straight portion 361, as shown in FIG. 3. This allows the fibrous conductive member to be inclined so that, in all of the first straight sections, the end of the fibrous conductive member on the first gas diffusion layer side is located downstream of the first straight section of the first gas flow path further than the end of the fibrous conductive member on the electrolyte membrane side.
[0075] The second electrode includes, in order from the electrolyte membrane side, a second catalyst layer and a second gas diffusion layer. The second separator has a second gas flow path. It is preferable to use the catalyst layer according to the present invention for both the first catalyst layer and the second catalyst layer.
[0076] As the electrolyte membrane, a polymer electrolyte membrane is preferably used. Examples of materials for the polymer electrolyte membrane include the polymer electrolytes exemplified as the proton conductive resin. The thickness of the electrolyte membrane is, for example, 5 to 30 μm.
[0077] The first gas diffusion layer and the second gas diffusion layer may have a structure having a substrate layer or may have a structure not having a substrate layer. An example of a structure having a substrate layer is a structure having a substrate layer and a microporous layer provided on the catalyst layer side. A conductive porous sheet such as carbon cloth or carbon paper is used for the substrate layer. A mixture of a water-repellent resin such as a fluororesin, a conductive carbon material, and a proton-conductive resin (polymer electrolyte) is used for the microporous layer.
[0078] The first separator and the second separator are not particularly limited in material as long as they have airtightness, electronic conductivity, and electrochemical stability. Such materials are preferably carbon materials, metal materials, and the like. Metal materials may be coated with carbon. For example, the first separator and the second separator are obtained by punching a metal plate into a predetermined shape and performing a surface treatment.
[0079] Hereinafter, an example of the structure of the fuel cell according to this embodiment will be described with reference to Fig. 4. Fig. 4 is a cross-sectional view that shows a schematic structure of a unit cell arranged in the fuel cell according to the embodiment of the present disclosure. Usually, a plurality of unit cells are stacked and arranged in the fuel cell as a cell stack. For convenience, Fig. 4 shows one unit cell.
[0080] A single cell of the fuel cell 200 includes an electrolyte membrane 110, and a first catalyst layer 120A and a second catalyst layer 120B arranged to sandwich the electrolyte membrane 110. The single cell of the fuel cell 200 further includes a first gas diffusion layer 130A and a second gas diffusion layer 130B arranged to sandwich the electrolyte membrane 110 with the first catalyst layer 120A and the second catalyst layer 120B interposed therebetween, and a first separator 240A and a second separator 240B arranged to sandwich the electrolyte membrane 110 with the first gas diffusion layer 130A and the second gas diffusion layer 130B interposed therebetween. One of the first catalyst layer 120A and the second catalyst layer 120B functions as an anode, and the other functions as a cathode. Since the electrolyte membrane 110 is slightly larger than the first catalyst layer 120A and the second catalyst layer 120B, the peripheral portion of the electrolyte membrane 110 protrudes from the first catalyst layer 120A and the second catalyst layer 120B. The peripheral portion of the electrolyte membrane 110 is sandwiched between a pair of sealing members 250A, 250B.
[0081] At least one of the first catalyst layer 120A and the second catalyst layer 120B is the catalyst layer 120 shown in Figures 5 and 6. Here, Figure 5 is a diagram showing a schematic view of the inside of the catalyst layer 120 as viewed from its surface direction (direction perpendicular to the first direction). For convenience, the electrolyte membrane 110 is also shown to show that the fibrous conductive members are inclined. Figure 6 is a diagram showing a schematic view of the inside of the catalyst layer 120 shown in Figure 5 as viewed from the gas diffusion layer side.
[0082] As shown in Figs. 5 and 6, the catalyst layer 120 includes a fibrous conductive member 121 and catalyst particles 122. As shown in Fig. 5, the fibrous conductive member 121 is inclined with respect to the surface direction of the electrolyte membrane 110. From the viewpoint of further improving the gas diffusibility of the catalyst layer, it is preferable that the inclination directions of the fibrous conductive members 121 are uniform when the inside of the catalyst layer is viewed from the surface direction, as shown in Fig. 5. As shown in Fig. 6, the length direction of the fibrous conductive members 121 is oriented on average in the first direction. When the first catalyst layer 120A or the second catalyst layer 120B is not the above-mentioned catalyst layer 120, a known material and a known configuration can be adopted as the catalyst layer.
[0083] In this embodiment, a gas flow channel 260A is formed on the surface of the first separator 240A that contacts the first gas diffusion layer 130A. On the other hand, a gas flow channel 260B is formed on the surface of the second separator 240B that contacts the second gas diffusion layer 130B. The shape of the gas flow channel is not particularly limited, and may be a parallel type, a serpentine type, or the like. When the first separator 240A or the second separator 240B does not have the gas flow channel 260A or 260B, a gas flow channel is formed on the surface of the corresponding gas diffusion layer that faces the separator.
[0084] The seal members 250A, 250B are made of an elastic material and prevent the fuel and / or oxidant from leaking from the gas flow paths 260A, 260B. The seal members 250A, 250B have, for example, a frame shape that surrounds the peripheral portions of the first catalyst layer 120A and the second catalyst layer 120B in a loop shape. The seal members 250A, 250B can each be made of a known material and have a known configuration.
[0085] The present disclosure will be described in more detail below with reference to examples, although the present disclosure is not limited to the following examples.
[0086] [Example 1] <Preparation of membrane electrode assembly> The fibrous conductive member carrying catalyst particles (Pt-Co alloy) was added to an appropriate amount of water, and then stirred to disperse. CNT (average diameter 15 nm, average fiber length 5 μm) was used as the fibrous conductive member. In this case, the catalyst particles were 30 parts by mass and the fibrous conductive member were 70 parts by mass relative to a total of 100 parts by mass of the catalyst particles and the fibrous conductive member. Next, an appropriate amount of ethanol was added to the obtained dispersion while stirring, and then 56 parts by mass of proton conductive resin (Nafion (registered trademark)) was added to 70 parts by mass of the fibrous conductive member. This was stirred to prepare a catalyst ink for the cathode side catalyst layer.
[0087] Separately, a catalyst ink for an anode-side catalyst layer was prepared in the same manner as the catalyst ink for a cathode-side catalyst layer, except that a particulate conductive material (carbon black) was used instead of a fibrous conductive material (carbon nanotubes).
[0088] Next, a Nafion membrane (registered trademark) with a thickness of 15 μm was prepared as the electrolyte membrane. Using a blade coater, the catalyst ink for the cathode side catalyst layer was applied in a uniform thickness to one surface of the electrolyte membrane, and dried to form a cathode side catalyst layer (thickness 6 μm). At this time, the catalyst ink was applied in one direction from one side of the opposing sides of the rectangular electrolyte membrane to the other side. The amount of catalyst ink applied was adjusted so that the thickness of the catalyst layer formed was 6 μm.
[0089] Next, the catalyst ink for the anode side catalyst layer was sprayed on the other surface of the electrolyte membrane in a uniform thickness and dried to form the anode side catalyst layer (thickness 6 μm). A frame-shaped seal member was placed so as to surround the anode side catalyst layer and the cathode side catalyst layer.
[0090] Two porous conductive carbon sheets were prepared as gas diffusion layers. One gas diffusion layer was placed in contact with the anode catalyst layer. The other gas diffusion layer was placed in contact with the cathode catalyst layer. In this manner, a membrane electrode assembly was produced.
[0091] <Preparation of a single cell> A bridge plate that guides the fuel or oxidant to each gas diffusion layer was placed near the manifold that had been formed in advance on the electrolyte membrane, and the whole was sandwiched between a pair of stainless steel flat plates (separators) to complete the test unit cell A1.
[0092] The separator used had a gas flow path with a parallel shape. The parallel gas flow path has a straight section including a plurality of gas flow paths arranged in parallel from one side to the other side of the separator. Gas flows in parallel from one side to the other side of the separator. The ratio of the length of the straight section to the length of the entire gas flow path was 100%, and the average flow direction of the gas flow path was the length direction of the straight section.
[0093] On the cathode side, the catalyst layer and the separator were arranged so that the direction in which the catalyst ink was applied onto the electrolyte membrane was perpendicular to the direction in which the gas flowed in the gas flow channel (straight portion).
[0094] The membrane electrode assembly obtained above was prepared separately, the cathode gas diffusion layer was removed, and the main surface of the cathode catalyst layer on the gas diffusion layer side was photographed by SEM. Using the SEM image, the first reference line (first direction) was obtained by the above-mentioned method, and when the cathode catalyst layer was viewed from a direction perpendicular to its surface direction, the angle θ d1 It was confirmed that the angle between the longitudinal direction of the fibrous conductive members was 30° or less. In other words, it was confirmed that the longitudinal direction of the fibrous conductive members was, on average, oriented in the first direction.
[0095] The angle θ between the first direction and the average flow direction of the gas flow path (direction of the straight portion) g was greater than 45°.
[0096] The membrane electrode assembly obtained above was separately prepared, and its cross section was photographed by SEM. From the SEM image, it was confirmed that a part of the catalyst particles was supported on the fibrous conductive member. The linearity L of the fibrous conductive member obtained by the above-mentioned method P The inclination angle θ of the fibrous conductive member with respect to the surface direction of the cathode-side catalyst layer, which was determined by the above-mentioned method, was 0.6 or more, and the linearity of the fibrous conductive member was ensured. c The angle θ was calculated by the method described above. d2was 30° or less, and it was confirmed that the inclination directions of the fibrous conductive members were uniform in the cross section along the thickness direction (first direction) of the cathode side catalyst layer.
[0097] The thickness T of the cathode side catalyst layer determined by the above-mentioned method was 6 μm. It was also confirmed by the above-mentioned method that the thickness of the catalyst layer was uniform. The length L of the fibrous conductive member determined by the above-mentioned method f was 5 μm. Therefore, L f / T was calculated to be 5 / 6.
[0098] <Evaluation> The power generation performance of the single cell A1 of Example 1 was evaluated. Specifically, fuel gas was supplied to the anode so that the utilization rate was 70%. The dew point of the fuel gas was about 80°C. Also, oxidant gas was supplied to the cathode so that the utilization rate was 50%. The dew point of the oxidant gas (air) was about 80°C. Then, the load control device was controlled so that the current flowed constantly, and the current density relative to the electrode area of the anode and cathode was changed. The maximum output density of the single cell A1 at this time was measured. The maximum output density is expressed as an index with the maximum output density of the single cell B1 of Comparative Example 1 taken as 100.
[0099] [Example 2] On the cathode side, the catalyst layer and the separator were arranged so that the direction in which the catalyst ink was applied onto the electrolyte membrane coincided with the direction in which the gas flowed through the gas flow channel (straight section). In this way, the inclination direction of the fibrous conductive member was aligned so that the end of the fibrous conductive member on the gas diffusion layer side was located downstream of the gas flow channel (straight section) relative to the end of the fibrous conductive member on the electrolyte membrane side. A unit cell A2 was otherwise fabricated and evaluated in the same manner as in Example 1.
[0100] The angle θ between the first direction and the average flow direction of the gas flow path (direction of the straight portion) g was 10° or less, and the first direction was oriented toward the average flow direction of the gas flow passage.
[0101] [Comparative Example 1] A single cell B1 was produced and evaluated in the same manner as in Example 1, except that the cathode-side catalyst layer was formed by spraying.
[0102] The cathode gas diffusion layer was removed from the obtained membrane electrode assembly, and the main surface of the catalyst layer on the gas diffusion layer side was photographed by SEM. The first reference line extending in the first direction was obtained by the above-mentioned method, and the angle θ between the first reference line extending in the first direction and the length direction of the fibrous conductive member when the catalyst layer was viewed from a direction perpendicular to the surface direction of the catalyst layer was measured. d1 As a result, the angle θ d1 It was confirmed that the inclination angle θ was greater than 30° and that the longitudinal direction of the fibrous conductive members was not oriented in the first direction on average. c was 25°.
[0103] The evaluation results are shown in Table 1.
[0104] [Table 1]
[0105] In the single cells A1 and A2 of Examples 1 and 2, the gas diffusivity of the catalyst layer was improved, and therefore a high maximum power density was obtained, compared with the single cell B1 of Comparative Example 1. Among them, the single cell A2 of Example 2 showed excellent power characteristics. [Industrial Applicability]
[0106] The fuel cell according to the present disclosure can be suitably used as a power source for a stationary type home cogeneration system or a power source for a vehicle. The invention according to the present disclosure is suitable for application to a polymer electrolyte fuel cell, but is not limited thereto, and can be applied to fuel cells in general. [Explanation of symbols]
[0107] 100 Membrane electrode assembly 110 Electrolyte membrane 120 Catalyst layer 120A 1st catalyst layer 120B 2nd catalyst layer 120X 1st main surface 120Y Second main surface 121 Fibrous conductive material 122 Catalytic particles 130A First gas diffusion layer 130B Second gas diffusion layer 200 Fuel Cell 240A First Separator 240B Second separator 250A, 250B sealing material 260A, 260B Gas flow path 360 First gas flow path 361 1st straight section 362 First Turn A1, A2, B1 single cell
Claims
1. A method for manufacturing a catalyst layer for a fuel cell, the catalyst layer having a uniform thickness and including a fibrous conductive member and catalyst particles, comprising the steps of: the fibrous conductive members are inclined with respect to a surface direction of the catalyst layer, and the length directions of the fibrous conductive members are oriented on average in a first direction; The length L of the fibrous conductive member is an average fiber length. f and the average thickness T of the catalyst layer are expressed by the following formula: 0.25≦L f / T≦2.0 is satisfied, The length L f is 0.5 μm or more and 10 μm or less, The thickness T is 2 μm or more and 20 μm or less, preparing an ink containing the fibrous conductive members and catalyst particles; a step of applying the ink to a surface of an electrolyte membrane and drying the ink to form the catalyst layer, or a step of applying the ink to a transfer substrate sheet and drying the ink to form a catalyst layer, and then transferring the catalyst layer to the electrolyte membrane.
2. 2. The method for manufacturing a catalyst layer for a fuel cell as described in claim 1, wherein, when the catalyst layer is viewed from a direction perpendicular to the surface direction, an average angle formed between a reference line extending in the first direction and a length direction of the fibrous conductive member is 30° or less.
3. A method for manufacturing a fuel cell including a membrane electrode assembly, and a first separator and a second separator sandwiching the membrane electrode assembly, comprising the steps of: the membrane electrode assembly includes an electrolyte membrane, and a first electrode and a second electrode sandwiching the electrolyte membrane; the first electrode includes, in order from the electrolyte membrane side, a first catalyst layer and a first gas diffusion layer; The method for producing a fuel cell, wherein the first catalyst layer is formed by the method for producing a catalyst layer according to claim 1 .
4. The first separator has a first gas flow path, The method for producing a fuel cell according to claim 3 , wherein the first direction is oriented in an average flow path direction of the first gas flow paths when viewed from a stacking direction of the membrane electrode assemblies.
5. the first gas flow path has a plurality of first linear portions facing the first direction, The method for producing a fuel cell according to claim 4 , wherein a ratio of a total length of the plurality of first straight portions to a total length of the first gas flow channel is 80% or more and 100% or less.
6. 6. The method for manufacturing a fuel cell according to claim 4 or 5, wherein in the first catalyst layer, the inclination direction of the fibrous conductive members is aligned so that the end of the fibrous conductive member on the first gas diffusion layer side is located downstream in the average flow path direction of the first gas flow path relative to the end of the fibrous conductive member on the electrolyte membrane side.
Citation Information
Patent Citations
Fuel cell and manufacture thereof
JP1991145062A
Fuel cell, and method for fabrication same
JP2007257886A
Cell for fuel cell, its manufacturing method, and polymer electrolyte fuel cell
JP2007273269A
Membrane electrode assembly and fuel cell, and manufacturing method therefor
JP2014035797A
Fuel cell membrane-electrode assembly
WO2013065396A1